Zakat as a Poverty Alleviation Instrument: A Case Study in Indonesia and Malaysia - Asmadia, Tezi; Suryadi, Ahmad; Asrida, Asrida; Utami, Sari (MD Research Center Yogyakarta, 2025)
The persistent of socio-economic inequality in Indonesia and Malaysia frames this study, which positions zakat as a potential religious-social instrument for economic empowerment. This research aims to critically compare the effectiveness of zakat management systems in both countries and analyze the factors influencing their performance. Employing a library research, this study conducts a systematic review and comparative analysis of academic literature, official publications from zakat institutions, government policy documents, and relevant reports spanning 2015-2023. The key findings indicate that system centralization and regulatory integration are pivotal; Malaysia’s state-coordinated system demonstrates higher collection efficiency and programmatic structure, while Indonesia’s decentralized model faces challenges in transparency, public trust, and infrastructural coordination that hinder optimal distribution. The conclusion argues that beyond political will, the effectiveness of zakat as an empowerment tool is fundamentally tied to institutional governance, professional management, and strategic alignment with broader economic policies, necessitating systemic reforms for greater impact.